Room-temperature copper-catalyzed electrophilic amination of arylcadmium iodides with ketoximes - Korkmaz, Adem (SPRINGER, 2021)
We started our study by preparation two ketoximes. Later, there were studies to reveal these ketoximes' effects in the electrophilic amination reaction with organocadmium reagents. Primarily, it was observed that arylcadmium iodides could not be reacted with ketoximes at room temperature in the absence of a catalyst. CuCN was a suitable catalyst for this electrophilic amination reaction of arylcadmium iodides and allowed the preparation of functionalized aniline derivatives in good yields under mild reaction conditions. We obtained the results indicated that the yield of primary arylamines was strongly dependent on the steric and electronic effects of organocadmium reagent and amination agent. In the case of both amination reagents, meta-substituted arylamines were obtained in higher yields than para-substituted arylamines. We observed that acetone O-(4-chlorophenylsulfonyl)oxime, 1, as an aminating agent, was more successful than acetone O-(2-Naphthylsulfonyl)oxime, 2, in the synthesis of functionalized arylamines by electrophilic amination of corresponding aryl cadmium iodides. In this method, there is no cadmium release to the environment.
Keywords: Electrophilic amination; Organocadmium reagents; Amines; Ketoximes; Catalysis; Organometallic